In Search of Lost Time : Swann's Way - Heuet, Stéphane (Liveright Publishing Corporation, 2015)
"Whether you are looking to brush up or sample for the first time, this graphic adaptation of "In Search of Lost Time" is the perfect introduction to Proust's masterpiece."--Dust jacket.